1994
DOI: 10.1139/a94-006
|View full text |Cite
|
Sign up to set email alerts
|

Land application of sewage sludge: scientific perspectives of heavy metal loading limits in Europe and the United States

Abstract: Heavy metals in sewage sludges accumulate in soils after successive sludge applications and can be toxic to plants, soil organisms, as well as humans and animals along the food chain. Because of this potential threat, many countries have set limits to the additions of metals in sludges to agricultural land, based on (i) the concentrations of metals in sludge itself, (ii) the loading, or total amount, of metal that can be added and often how quickly this can be applied, and (iii) the maximum concentrations of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
1
8

Year Published

1996
1996
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 188 publications
(97 citation statements)
references
References 14 publications
1
87
1
8
Order By: Relevance
“…FLI improved the polyphenol level which indicates the superior performance of isolate to decrease the salt stress. McGrath et al (1994) also reported that the inoculation of crops with organic waste accumulates the antioxidants. The presence of feather-degraded lysate in bioformulation is also contributed for increase in polyphenol content of wheat crops exposed to salinity (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…FLI improved the polyphenol level which indicates the superior performance of isolate to decrease the salt stress. McGrath et al (1994) also reported that the inoculation of crops with organic waste accumulates the antioxidants. The presence of feather-degraded lysate in bioformulation is also contributed for increase in polyphenol content of wheat crops exposed to salinity (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Their accumulation in cropland soils poses a potentially serious threat to human and ecosystem health (de Meeus et al, 2002;Hinwood et al, 2004). To ensure that trace element levels in crops produced for human consumption do not cause unacceptable risks to the consumer health, regulatory authorities have established numerical limits for nonnutritive elements in fertilizers and other soil amendments based on outcomes of risk assessments (McGrath et al, 1994;Chen et al, 2007a).…”
Section: Introductionmentioning
confidence: 99%
“…The fact that Cu tends to accumulate in the surface layers of many soils (McBride 1981 ;McGrath et al 1994) indicates that it is in stable forms which protect the Cu from being absorbed by plants or lost from the soil in drainage water.…”
Section: Water Contaminationmentioning
confidence: 99%